(untitled) (Jurnal ForestrIndo, 2025)
Sungai Buluh Village has 26% forest cover in its Other Land Use Area (APL) which is threatened by land conversion. This threat requires efforts to protect the remaining forest cover by utilizing alternative forest resources in the area. One alternative utilization that can be developed is fruit as a Non-Timber Forest Product (NTFP). For this reason, it is necessary to conduct an analysis of the physical potential and economic value of fruit through field observations, forest inventory, interviews, Focus Group Discussions (FGD) and calculation of economic value. The results show that there are 15 species of fruit, but only 4 species have commercial value, namely durian (Durio sp.), jengkol (Pithecellobium jiringa), keranji (Dialium indum), and longan (Dimocarpus longan L.). Keranji has the highest production potential with 280,746 kg/year, followed by durian with 256,220 fruits/year, jengkol with 58,610 kg/year, and longan with 2,812 kg/year. Durian and jengkol have high resource rent values of Rp 3.751.280/ha/year and Rp 3.351.280/ha/year, respectively. The highest utilization rates are for durian (29%) and jengkol (46%). Sustainable forest resource management and the economic utilization of NTFPs are necessary strategies to enhance community welfare and protect the environment in Sungai Buluh village.